Potential for a cerebellar role in moderate-late preterm associated behavioural disorders - Carlton L. Pavy; Carlton L. Pavy; Julia C. Shaw; Julia C. Shaw; Roisin A. Moloney; Roisin A. Moloney; Hannah K. Palliser; Hannah K. Palliser; Jonathon J. Hirst; Jonathon J. Hirst (Frontiers in Pediatrics, 2024)
Preterm birth is known to cause impaired cerebellar development, and this is associated with the development of neurobehavioral disorders. This review aims to identify the mechanisms through which preterm birth impairs cerebellar development and consequently, increases the risk of developing neurobehavioral disorders. The severity of these disorders is directly related to the degree of prematurity, but it is also evident that even late preterm births are at significantly increased risk of developing serious neurobehavioral disorders. Preterm birth is associated with hypoxic events and increased glutamatergic tone within the neonatal brain which contribute to excitotoxic damage. The cerebellum is a dense glutamatergic region which undergoes relatively late neurodevelopment up to and beyond birth. Evidence indicates that the cerebellum forms reciprocal connections to regions important in behaviour regulation such as the limbic system and frontal cortex. Studies using fMRI (functional magnetic resonance Imaging), BOLD (blood oxygen level dependent) response and morphology studies in humans show the cerebellum is often involved in disorders such as attention deficit hyperactivity disorder (ADHD) and anxiety. The vulnerability of the cerebellum to preterm birth insult and its connections to behaviour associated brain regions implicates it in the development of neurobehavioral disorders. Protection against preterm associated insults on the cerebellum may provide a novel avenue through which ADHD and anxiety can be reduced in children born preterm.